Organizational happiness and its association with organizational commitment: A mixed-methods study among private school teachers in Türkiye - Sema İncekara; Ahmet Şahin (PLoS ONE, 2026)
Background Teaching is demoralizing, challenging, and stressful for many teachers. Greater student achievement requires better teacher performance and happiness. An effective school climate in which teachers feel positive emotions is crucial for employing happy and quality teachers. However, given the pressures of the competitive private education sector on teachers, organizational well-being and commitment in the private school setting in Türkiye remain a research gap. Hence, this study aimed to examine the relationship between organizational happiness and organizational commitment of private school teachers, focusing on the factors affecting teachers’ happiness and commitment. Methods We conducted a sequential explanatory mixed-methods study. Data from 299 private school teachers were collected for the quantitative strand, while eight teachers from various private schools participated in the qualitative strand. Multiple linear regression analyses were conducted on the quantitative data to examine the relationship between organizational commitment and happiness. Qualitative data were analyzed using thematic analysis with an inductive approach. Results The quantitative results revealed high positive affect, fulfillment, affective commitment, and normative commitment, but moderate negative affect and continuance commitment. Positive affect and fulfillment were significantly and positively related to affective, continuance, and normative commitment, whereas negative affect was negatively related to them. Qualitative interviews supported these findings. Positive emotions and supportive work conditions are likely to enhance commitment; however, negative work-related factors may reduce it. Despite their strong affective and normative commitments, teachers’ intentions to remain in school remain unclear. Conclusions The study revealed that enhancing teachers’ happiness and creating environments for fulfillment are likely to enhance organizational commitment, whereas reducing negative workplace emotions is vital. Qualitative insights enrich these results by illustrating the factors influencing happiness, such as positive emotions and supportive work conditions, which enhance commitment. Fostering positive effects and decreasing negative factors are key to increasing teachers’ organizational commitment through enhanced happiness.